Effect-based methods and effect-based trigger values for estrogenicity monitoring in surface water: an interlaboratory study - Livia Gómez; Dimitar Marinov; Elena Porcel-Rodríguez; Diletta Scaccabarozzi; Isabella Sanseverino; Pietro Sciuto; Frank Narendja; Romana Hornek-Gausterer; Katharina Lenz; Carole Chalon; Yves Marneffe; Přemysl Soldán; et al. (Environmental Research, 2026)

Effects of pesticide use, microhabitat structure, and landscape diversity on arthropod communities, pest–disease dynamics, and yield in cacao agroecosystems - Bladimir Guaitero; Diego Fernando Cuero-Plaza; David Ricardo Hernández-Angarita; Hebert Camargo-Tamayo; Carolina Pisco-Ortiz; Edwin Rodríguez; Paola Zuluaga; Mario Porcel; Yeisson Gutiérrez (Agriculture, Ecosystems & Environment, 2026)

Preparing Colombian coffee production for climate change: Integrated spatial modelling to identify potential robusta coffee (Coffea canephora P.) growing areas - Carlos E. González-Orozco; Mario Porcel; Vivekananda Mittahalli Byrareddy; Eric Rahn; William A. Cardona; Diego A. Salinas Velandia; Gustavo A. Araujo-Carrillo; Jarrod Kath (Climatic Change, 2024)
Meeting future demand for coffee under climate change is a challenge. Approaches that can inform where coffee may grow best under current and future climate scenarios are needed. Robusta coffee ( Coffea canephora P.) is planted in many tropical areas and makes up around 40% of the world’s coffee supply. However, as the climate shifts, current robusta areas may become less productive, while in other areas new growing regions for robusta may emerge. Colombia is one of the world’s most important Arabica coffee producer, famous for its high-quality coffee. Although robusta coffee is not yet a commercial crop in Colombia, it could be one of the future bastions for robusta coffee in South America contributing to meeting the increasing demand, but this remains unexplored. We aimed to identify areas with highest biophysical and socio-economic potential to grow robusta coffee in Colombia. An integrated modelling approach was used, combining climate suitability and crop-yield modelling for current and future climate scenarios, soil constraints, pest risk assessment and socio-economic constraints to identify the regions with the highest potential productivity and the lowest pest and climate change risks with good market access and low security risks which don’t further expand the agricultural frontier. Our results showed that parts of the foothills along the eastern Andean Mountain ranges, the high plains of the Orinoquía region and the wet parts of the Caribbean region are the best candidates for the potential development of robusta coffee plantations in Colombia. The crop-yield model indicated highest yields of green coffee on the foothills of the eastern Andean Mountain range with an estimated average yield of 2.6 t ha −1 (under rain-fed conditions) which is projected to occur at elevations below 600 m avoiding interference with the traditional and established Arabica coffee regions in Colombia. Under a 2 °C global warming scenario climate change is projected to have the largest impacts on the Caribbean region. Therefore, larger scale irrigated production system could be an appropriate option in the Caribbean region, while diversified smallholder robusta coffee agroforestry systems are considered more favourable in the Orinoquía region.

Using flower strips to promote green lacewings to control cabbage insect pests - Rafael Alcalá Herrera; Belén Cotes; Nuria Agustí; Marco Tasin; Mario Porcel (Journal of Pest Science, 2022)
Habitat management improves biological control by increasing the abundance and fitness of natural enemies through the provision of floral resources along field edges or between crops. Among the natural enemies reliant on flower resources, green lacewings often stand out due to their abundance, predation capacity and polyphagy. We evaluated the impact of tailored flower strips on the enhancement of natural enemies, especially green lacewings, in three organic cabbage ( Brassica oleracea ) farms in Southern Sweden. Insects were sampled from the flower strips, and cabbage pests and predators were visually recorded in the crop. In a laboratory assay, the pollen feeding preferences of Chrysoperla carnea (Stephens, 1836) were evaluated in a dual-choice test. The pollen consumed by the Chrysopidae was extracted from laboratory and field specimens, then quantified and identified. Flower strips were found to attract predators and parasitoids, whose abundance increased as flowers bloomed. Cabbage plants next to the flower strips showed lower pest infestation as compared to cabbage plant control, although no significant differences were observed in the number of predators. Chrysopidae used flower strips as feeding, reproduction and shelter sites and mainly consumed pollen from Phacelia tanacetifolia Benth. Under laboratory conditions, C. carnea showed a preference for P. tanacetifolia and Coriandrum sativum L. pollen over Borago officinalis L. and Fagopyrum esculentum Moench. We show that tailored flower strips could be an efficient tool for enhancing beneficial arthropods and should be considered in integrated pest management for cabbage crops.

Attract, reward and disrupt: responses of pests and natural enemies to combinations of habitat manipulation and semiochemicals in organic apple - Joakim Pålsson; Mario Porcel; Teun Dekker; Marco Tasin (Journal of Pest Science, 2022)
The widespread use of pesticides along with the simplification of the landscape has had undesirable effects on agroecosystems, such as the loss of biodiversity and the associated ecosystem service biological control. How current production systems can be remodelled to allow for a re-establishment of biological pest control, while preserving productivity, is a major challenge. Here, we tested whether a combination of tools could augment or synergize biological control of insect pests in apple ( Malus domestica ), comprised of a tortricid pest complex , a geometrid pest complex and the rosy apple aphid. The tools aimed at disrupting mating behaviour of multiple pest species (multispecies mating disruption, “Disrupt”, MMD), attracting natural enemies (a blend of herbivory-induced volatiles, “Attract”, A), or providing refuge and rewards for a diverse insect community (perennial flower strip, “Reward”, R) over a 3-year period. Suction samples were consistently richer in generalist predators but not in parasitoids when multiple tools including MMD + A + R or MMD + A were employed. In addition, lepidopteran pest levels were significantly lower in these plots than in MMD or MMD + R at the end of the 3-year experiment. This was, however, not reflected in survival of artificially established aphid colonies. Our data indicates that multiple, complementary tools can greatly enhance natural enemy level, but also that long-term implementation is needed to fully realize the augmentatory or synergistic potential of complementary components and restore biological control as an ecosystem service of practical relevance.

Extreme climate refugia: a case study of wild relatives of cacao (Theobroma cacao) in Colombia - Carlos E. González-Orozco; Mario Porcel; Caren Rodriguez-Medina; Roxana Yockteng (Biodiversity and Conservation, 2022)

Two centuries of changes in Andean crop distribution - Carlos E. González‐Orozco; Mario Porcel (Journal of Biogeography, 2021)
Aim Historical changes in crop distributions of tropical regions are poorly understood and rarely quantified due to the scarcity of historical records. As early as 1796, Francisco José de Caldas recorded crop distribution and drew maps depicting crop regions for eight crops. Using Caldas’ crop regions, we identify changes of crop distribution in relation to latitude and elevation, as well as compare their elevational limits over two centuries. Location The northern Andean mountain range between Colombia and Ecuador. Taxon Wheat, barley, potato, maize, sugarcane, cacao, plantain and cassava. Methods We analysed Caldas’ crop regions and compared them with a current homologous replication of the same crops. We tested whether elevational ranges and mean elevation of the crops varied between the colonial and contemporary periods and analysed the relationship between elevation and latitude. Results In quantifying the historical and contemporary distributions, we identified a large expansion of 740.1 meters in the elevational range over 224 years for all eight crops. We also found crops located at lower latitudes south towards Quito distributed at a higher elevation. Main conclusions Our findings use historical data never used before to investigate the evolution of crop distribution since the colonial period. Our analysis provides evidence to conclude that Caldas’ work on climate and agriculture was essential to developing the field of tropical agriculture climatology, a discipline for which Caldas established but was never given recognition.

The effect of resident vegetation cover on abundance and diversity of green lacewings (Neuroptera: Chrysopidae) on olive trees - Mario Porcel; B. Cotes; J. Castro; M. Campos (Journal of Pest Science, 2017)

Weeds within willow short-rotation coppices alter the arthropod community and improve biological control of the blue willow beetle - Jörg G. Stephan; Johannes Albertsson; Liying Wang; Mario Porcel (BioControl, 2016)